Critical analysis of the law regulating state intervention in the mineral sector and nationalisation of South African mines - Mafa, Mmapau Justin (My University, 2013)
This mini-dissertation relates to the mode of ownership of the country’s natural, mineral and petroleum resources, their contribution to the economy, the Growth Domestic Income and the overall role played by these resources to better the lives of the ordinary citizens and their impact on the socio economic circumstances in general. In terms of the previous mining legislation in South Africa, mineral rights were held privately and in some instances by the state. Following the 1994 democratic breakthrough, the Mineral and Petroleum resources Development Act now vests the ownership of mineral rights in the state as the custodian and owner on behalf of the people of South Africa and the mineral resources are the common heritage of the people. The vesting of the mineral rights does not however interfere with the right to private ownership of property which is expressly guaranteed by the property clause in the constitution. The new Mining legislative regime with specific and particular reference to the Mineral and Petroleum Resources Development Act and National Environmental Management Act are precisely paced to ensure optimal exploitation of natural resources while promoting sustainable development.
Thesis (LLM. (Development and Management Law)) -- University of Limpopo, 2013
Keywords: Growth Domestic Income; Resource Development Act; South African Constitution; Mines and mineral resources - Government ownership - Law and legislation -- South Africa; Government ownership